Ethical consumption behaviours in supermarket shoppers: determinants and marketing implications. Issue 7 (3rd May 2016) - Jayawardhena, Chanaka; Morrell, Kevin; Stride, Chris
ABSTRACT: Understanding how consumers make ethical purchases has numerous benefits for firms and other stakeholders. Although several ethical decision-making frameworks seek to explain such purchasing behaviour, they typically focus on the content of such decisions, rather than considering how such decisions unfold in a given context. Yet, the complexities of consumer choice suggest that greater insight into how consumers make ethical purchases in store can enhance understanding. We report our findings from a survey of a geographically disperse sample of 688 UK shoppers and argue that a naturalistic theory of decision making, image theory, enhances our ability to explain consumer behaviour in this setting. As well as contributing to theoretical understanding of consumer choice, this has implications for the merchandising of ethical products, such as Fair Trade and 'green' goods.